Sub-Gaussian Type Estimates for Symmetric Random Variable - Ghimire, Santosh (Journal of Institute of Science and Technology, 2023)
Sub-Gaussian type estimates are crucial when investigating the asymptotic behavior of symmetric independent random variables. This article aims to establish some sub-Gaussian type estimates for these variables, specifically for the summation of first number of variables and for the tail sums of those variables. We derive three such estimates.